Effect of isokinetic muscle strength training on knee muscle strength, proprioception, and balance ability in athletes with anterior cruciate ligament reconstruction: a randomised control trial - Wang, Kun; Cheng, Liang; Wang, Bingcheng; He, Benxiang (Frontiers in Physiology, 2023)
Objective: This study aimed to investigate the effects of regular isokinetic muscle strength training on knee muscle strength, proprioception, and balance ability in athletes after anterior cruciate ligament (ACL) reconstruction. Methods: Forty-one athletes who underwent ACL reconstruction were randomly divided into the experimental (n = 21) and control (n = 20) groups. The experimental group used an isokinetic muscle strength tester for 4 weeks (five times/ week) of knee flexion and extension isokinetic muscle strength training. The control group used the knee joint trainer (pneumatic resistance) for the same exercise regimen as the experimental group. Results: 1) Four weeks when compared with the baseline. Experimental group: the knee flexion and extension PT (60°/s and 240°/s) increased by 31.7%, 40.3%, 23.4%, and 42.9% (p < 0.01), and the flexion muscular endurance increased by 21.4% and 19.7% (p < 0.01). The flexion and extension kinaesthesia and the 30° and 60° position sense decreased by 36.2%, 32.3%, 40.0%, and 18.9% (p < 0.05). The anterior–posterior and medial–lateral displacement and speed decreased by 30.2%, 44.2%, 38.4%, and 24.0% (p < 0.05). Control group: the knee peak torque (60°/s) increased by 18.8% (p < 0.01). The anterior–posterior and medial–lateral displacement and speed decreased by 14.9%, 40.0%, 26.8%, and 19.5% (p < 0.01). 2) After 4 weeks, compared with the control group, the knee flexion and extension peak torque (60°/s), extension, peak torque (240°/s), and extension muscular endurance of the treatment group increased to varying degrees (p < 0.05). However, the kinaesthesia, 30° position sense, and anterior–posterior displacement decreased to varying degrees (p < 0.05). Conclusion: Adding regular isokinetic muscle strength training to rehabilitation training further improved the knee flexion and extensor strength and extensor endurance of athletes with ACL reconstruction, as well as enhanced the kinaesthesia and 30° position sense and the balance between the anterior and posterior directions. However, the treatment had limited effects on knee flexion kinaesthesia and muscle endurance.